2017
DOI: 10.2147/ijnrd.s136522
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life in patients undergoing hemodialysis using WHOQOL-BREF questionnaire: a multicenter study

Abstract: Background Assessment of quality of life (QOL) of patients with end-stage renal disease has become increasingly important, both in order to evaluate the influence of the disease on patients and the type of renal replacement therapy they require. Therefore, in this study, we aimed to assess QOL in patients undergoing hemodialysis and evaluated the effects of various sociodemographic factors affecting QOL of such patients in Nepal. Methods A cross-sectional study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
3
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 24 publications
8
54
3
9
Order By: Relevance
“…The lower QOL in physical domain in dialysis patients than transplant patients can be attributed to physical pain, weakness, insomnia and hindrance to daily activities as identi ed in previous studies [32,33]. A study previously done in Nepal also had pointed increased duration of hameodialaysis as a negative predictor of QOL [34].Similarly, the reason for renal transplant patients having a higher QOL in psychological domain might be due to decrease in mental burden resulting from having to visit health facility for frequent dialysis. Similarly, the increased self-esteem and improved perception regarding own health might have contributed to good mental wellbeing among renal transplant patients [26].…”
Section: Discussionmentioning
confidence: 73%
“…The lower QOL in physical domain in dialysis patients than transplant patients can be attributed to physical pain, weakness, insomnia and hindrance to daily activities as identi ed in previous studies [32,33]. A study previously done in Nepal also had pointed increased duration of hameodialaysis as a negative predictor of QOL [34].Similarly, the reason for renal transplant patients having a higher QOL in psychological domain might be due to decrease in mental burden resulting from having to visit health facility for frequent dialysis. Similarly, the increased self-esteem and improved perception regarding own health might have contributed to good mental wellbeing among renal transplant patients [26].…”
Section: Discussionmentioning
confidence: 73%
“…QOL under physical domain was lower than the other domain and QOL under environmental domain was higher than the other domains. Similarly, a study done in Nepal revealed that patients with CKD undergoing dialysis had overall low QOL scores in all four domains (Joshi et al, 2017).…”
Section: Comparison Of Overall Qol With Demographic Datamentioning
confidence: 92%
“…Another study found that participants of higher education had a better quality of life, possibly because education allows an in-depth understanding of the disease and compliance with the therapeutic regimen. Another alternative explanation is that higher education may reflect higher income and consequently, the ability to afford treatment (Gerasimoula et al, 2015). A similar study conducted in Iran revealed that older age, female gender, and lower educational level were significantly associated with a lower score of all physical, psychological, and social domains of QOL (Tilaki et al, 2017).…”
Section: Comparison Of Overall Qol With Demographic Datamentioning
confidence: 99%
“…whilst the lowest was in the social relationship domain (9.5). However, the low score in the social domain was expected as it was based on three items instead of the four recommended for assessing internal reliability [37]. The low alpha score in the psychological domain (0.59) could be attributed to the limited number of valid responses (n=16) or the poor interrelatedness between the items [38].…”
Section: Participant Characteristicsmentioning
confidence: 99%